Utilizing the Attention Economy as A Means of Actualizing Santripreneurs - mochammad Sabiq Al Hadi Sabiq; Intan Putri Nazila (HARAMAIN: Jurnal Manajemen Bisnis, 2026)
The rapid growth of the digital economy has transformed entrepreneurship from being primarily based on physical capital to one increasingly driven by public attention. However, studies on the role of the attention economy in developing santripreneurship within Islamic boarding schools remain limited. This study aims to examine the utilization of the attention economy as a form of santripreneur actualization at Pondok Pesantren Roudhotun Nafiiyah Pasuruan and to formulate an attention economy-based santripreneur model. This research employed a qualitative case study approach. Data were collected through observations, in-depth interviews, and documentation involving pesantren leaders, entrepreneurship program managers, and santri. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that the attention economy is implemented through digital content creation, social media management, promotion of student products, and dissemination of pesantren activities. Public attention functions as digital capital that can be transformed into trust, reputation, social networks, and entrepreneurial opportunities. The study also found that Islamic values, including amanah, honesty, responsibility, and maslahah, guide attention economy practices. Based on these findings, this study proposes an attention economy-based santripreneur model that integrates digital engagement, entrepreneurship, and Islamic values. The study contributes to Islamic entrepreneurship literature by introducing attention as a strategic capital for santripreneur development in the digital era.